Parametric study of the impact of window attachments on air conditioning energy consumption. (15th May 2020) - Tan, Yutong; Peng, Jinqing; Curcija, Dragan C.; Hart, Robert; Jonsson, Jacob C.; Selkowitz, Stephen
Highlights: A comprehensive parametric study of roller shades and cellular shades. Identify key parameters affecting window attachment's energy performance through simulation results. Sensitivity analysis of different parameters. A new index for a unified assessment of different window attachments. Abstract: This paper investigated the energy performance of window attachments and analyzed the impact of window attachments' parameters on air conditioning energy consumption of residential buildings in a cooling-dominated city (Houston) and a heating-dominated city (Minneapolis). Roller and cellular shades were selected as research objects in this study. Nine parameters related to window attachment energy performance were chosen as the probable important influence factors for the parametric study. Three values, high, medium and low levels, were set for each parameter, resulting in a total of 9520 (roller) and 9072 (cellular) combinations respectively. The optical and thermal properties of each combination were calculated with Berkeley Lab WINDOW program before coupling with an EnergyPlus typical residential building model. Based on simulation results, an annual energy performance (AEP) index was proposed to rate the energy saving potential of window attachments. Key parameters which have significant impacts on air conditioning energy consumption were determined through the parameter sensitivity analysis. The research results indicated that solar transmittance and solar reflectance are the most influential factors to the energy performance of window attachments among the nine selected parameters. The current cellular shade could achieve the AEPh and AEPc of 0.19 and 0.12. Among all combinations, the best AEPh and AEPc of cellular shades are 0.68 and 0.89, respectively. Besides, as for roller shades, the current level of AEPh and AEPc are 0.14 and 0.09, and the optimal AEPh and AEPc are 0.43 and 0.79.